Development strategies of dairy products of companies of the state of São Paulo (Brazil) - Silva, A. L. [UNESP]; Santini, G. A. [UNESP]; Queiroz, T. R. [UNESP] (My University, 2011)
This article aims at analyzing the strategic actions - product development - companies from the dairy sector, specifically, the processing companies and also national, multinational, located in São Paulo state (Brazil). The methodology was based primarily on a literature review of theories of innovation and differentiation (its importance and strategies used by companies) and, subsequently, in a practice research, with six companies with Federal Inspection System, set to the state of Sao Paulo. The sampling was aleatory or non-probabilistic nature, according to the company's ability to participate. The analysis concluded that the companies interviewed, though not develop a greater number of innovations of a complex mode (new products and novelty global and national) are seeking to permanently differentiation, even that packaging or design improved, they are able to 'provoke' a greater desire by the consumer, which is contributing to increased consumption of milk by the population.
Keywords: Companies; Dairy; Processing; Product innovation; Production; Strategies